ESE3/EHF, a promising target of rosiglitazone, suppresses pancreatic cancer stemness by downregulating CXCR4. Issue 2 (5th March 2021) - Zhou, Tianxing; Liu, Jing; Xie, Yongjie; Yuan, Shuai; Guo, Yu; Bai, Weiwei; Zhao, Kaili; Jiang, Wenna; Wang, Hongwei; Wang, Haotian; Zhao, Tiansuo; Huang, Chongbiao; et al.
Abstract : Background and aims: The crosstalk between cancer stem cells (CSCs) and their niche is required for the maintenance of stem cell-like phenotypes of CSCs. Here, we identified E26 transformation-specific homologous factor (EHF) as a key molecule in decreasing the sensitivity of pancreatic cancer (PC) cells to CSCs' niche stimulus. We also explored a therapeutic strategy to restore the expression of EHF. Design: We used a LSL-Kras G12D/+ mice, LSL-Trp53 R172H/+ and Pdx1-Cre (KPC) mouse model and samples from patients with PC. Immunostaining, flow cytometry, sphere formation assays, anchorage-independent growth assay, in vivo tumourigenicity, reverse transcription PCR, chromatin immunoprecipitation (ChIP) and luciferase analyses were conducted in this study. Results: CXCL12 derived from pancreatic stellate cells (PSCs) mediates the crosstalk between PC cells and PSCs to promote PC stemness. Tumorous EHF suppressed CSC stemness by decreasing the sensitivity of PC to CXCL12 stimulus and inhibiting the crosstalk between PC and CSC-supportive niches. Mechanically, EHF suppressed the transcription of the CXCL12 receptor CXCR4. EHF had a cell autonomous role in suppressing cancer stemness by inhibiting the transcription of Sox9, Sox2, Oct4 and Nanog . Rosiglitazone suppressed PC stemness and inhibited the crosstalk between PC and PSCs by upregulating EHF. Preclinical KPC mouse cohorts demonstrated that rosiglitazone sensitised PDAC to gemcitabine therapy. Conclusions: EHF decreased the sensitivity of PC to the stimulus from PSC-derived CSC-supportive niche by negatively regulating tumorous CXCR4. Rosiglitazone could be used to target PC stem cells and the crosstalk between CSCs and their niche by upregulating EHF.